From synthesis to formulation of gliclazide and glibenclamide cocrystal pharmaceutical solid dosage forms - Baptista, Bárbara Violinha (2018)
Tese de mestrado, Engenharia Farmacêutica, Universidade de Lisboa, Faculdade de Farmácia, 2017